2021
DOI: 10.1111/raq.12592
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of the variable response of microalgal lipids to culture salinity

Abstract: Salinity is an important factor in microalgal mass production that has been less studied than other external factors such as temperature and irradiance. The greater attention paid to the effects of these two factors reflects the important influence that both exert on growth and production of microalgae. 1 However, the ability to control the effects of temperature and irradiance on microalgal production is inversely proportional to the size of the culture system. This especially affects outdoor mass production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 212 publications
0
4
0
Order By: Relevance
“…Many companies and institutions have well demonstrated the industrial scale photobioreactor system for marine hatcheries (Naumann et al, 2013;Tibbetts et al, 2020). Several studies have showed that manipulations in culture conditions and composition of fertilizer could affect microalgal productivity and nutritional quality (Harrison et al, 1990;Reitan et al, 1994;Reitan et al, 1997;Cañavate, 2019;Han et al, 2019;Cañavate and Fernańdez-Dıáz, 2022). In this research topic, Latsos et al revealed a significant increase of fatty acid levels in the microalga Rhodomonas sp.…”
Section: Live Feed Production For Marine Larviculturementioning
confidence: 99%
“…Many companies and institutions have well demonstrated the industrial scale photobioreactor system for marine hatcheries (Naumann et al, 2013;Tibbetts et al, 2020). Several studies have showed that manipulations in culture conditions and composition of fertilizer could affect microalgal productivity and nutritional quality (Harrison et al, 1990;Reitan et al, 1994;Reitan et al, 1997;Cañavate, 2019;Han et al, 2019;Cañavate and Fernańdez-Dıáz, 2022). In this research topic, Latsos et al revealed a significant increase of fatty acid levels in the microalga Rhodomonas sp.…”
Section: Live Feed Production For Marine Larviculturementioning
confidence: 99%
“…Both hyposalinity and hyper-salinity have an effect of cell growth rate, cell volume and biomass composition, especially on lipid fraction and composition. In Nannochloropsis, the lipid fraction generally increases with decreasing salinity, with the same applying to the EPA lipid fraction [25]. Salt stress has also been used to increase carotenoid content, especially in freshwater species such as Haematococcus pluvialis [26].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids are important structural components of membranes and energy reserves, so adjustments to lipid metabolism are essential for the osmotic stress response. It has been noted that microalgae, as well as higher plants, alter their lipid content and composition under drought or salinity stress, mainly due to membrane remodelling (Guo et al, 2019), lipid accumulation or utilization of lipid stores (Cañavate & Fernández-Díaz, 2022). In particular, changes in membrane lipids involving the desaturation of fatty acids can increase membrane fluidity and improve photosynthesis (Sui et al, 2010;Guo et al, 2019), as well as enhance the performance of ion transporters (Zhang et al, 2002).…”
Section: Metabolismmentioning
confidence: 99%
“…However, the inverse mechanismi.e., decreased unsaturation-protects against ROS (Kan et al, 2012), reducing lipid peroxidation and, in turn, decreasing leakage of inorganic ions through the membranes (Filek et al, 2012). Diverse responses have been observed, though, as a result of osmotic stress, with species increasing (López-Pérez et al, 2009;Shetty et al, 2019) or decreasing (Kan et al, 2012) fatty acid unsaturation and species accumulating or reducing their lipid stores (Cañavate & Fernández-Díaz, 2022). When assessing different methods for the cryopreservation of Symbiodiniaceae, Kihika et al…”
Section: Metabolismmentioning
confidence: 99%